Interaction Between CD34+ Fibrocytes and Airway Smooth Muscle Promotes IL-8 Production and Akt/PRAS40/mTOR Signaling in Asthma - Lin, Ting-Yu; Chang, Po-Jui; Lo, Chun-Yu; Lo, Yu-Lun; Yu, Chih-Teng; Lin, Shu-Min; Kuo, Chih-His Scott; Lin, Horng-Chyuan (Frontiers in Medicine, 2022)
Background The circulating progenitor cells of fibroblasts (fibrocytes) have been shown to infiltrate the airway smooth muscle compartment of asthma patients; however, the pathological significance of this discovery has yet to be elucidated. This study established a co-culture model of airway smooth muscle cells (ASMCs) and fibrocytes from asthmatic or normal subjects to evaluate innate cytokine production, corticosteroid responses, and signaling in ASMCs. Methods CD34+ fibrocytes were purified from peripheral blood of asthmatic (Global Initiative for Asthma treatment step 4–5) and normal subjects and cultured for 5∼7 days. In a transwell plate, ASMCs were co-cultured with fibrocytes at a ratio of 2:1, ASMCs were cultured alone (control condition), and fibrocytes were cultured alone for 48 h. Measurements were obtained of interleukin-8 (IL-8), IL-6, IL-17, thymic stromal lymphopoietin, and IL-33 levels in the supernatant and IL-33 levels in the cell lysate of the co-culture. Screening for intracellular signaling in the ASMCs after stimulation was performed using condition medium from the patients’ co-culture (PtCM) or IL-8. mRNA and western blot analysis were used to analyze AKT/mTOR signaling in ASMCs stimulated via treatment with PtCM or IL-8. Results Compared with ASMCs cultured alone, IL-8 levels in the supernatant and IL-33 levels in the ASMCs lysate were significantly higher in samples co-cultured from asthmatics, but not in those co-cultured from normal subjects. Corticosteroid-induced suppression of IL-8 production was less pronounced in ASMCs co-cultured with fibrocytes from asthma patients than in ASMCs co-cultured from normal subjects. ASMCs stimulated using PtCM and IL-8 presented elevating activated AKT substrate PRAS40. Treatment with IL-8 and PtCM increased mRNA expression of mTOR and P70S6 kinases in ASMCs. Treatment with IL-8 and PtCM also significantly increased phosphorylation of AKT and mTOR subtract S6 ribosomal protein in ASMCs. Conclusion The interaction between ASMCs and fibrocytes from asthmatic patients was shown to increase IL-8 and IL-33 production and promote AKT/mTOR signaling in ASMCs. IL-8 production in the co-culture from asthmatic patients was less affected by corticosteroid than was that in the co-culture from normal subjects. Our results elucidate the novel role of fibrocytes and ASMCs in the pathogenesis of asthma.